Effect of Executive Characterics and Firm Size on Tax avoidance - Pujiastuti, Heni; Subkhan, Farid (International Journal of Applied Management and Business, 2023)
Purpose – This study seeks to determine the extent of the role of the executive in playing its policies in determining the cost of taxes.Methodology/approach – To find out more about executive capabilities in determining tax policy, financial statements from issuer manufacturing companies for the 2015 - 2019 period were used. All data was obtained by purposive sampling. SPSS 25 is used in analyzing data and answering the objectives of this study.Findings – The role of Executive  Characteristics has no  influence on Tax Avoidance. Tax Avoidance is influenced by  Executive Characteristics and Firms Size. This is because  executives do not have the  desire to  do tax  avoidance through things that are possible  to  reduce tax payments, taking advantage of transactions that are of  a nature  related parties between branches within the company,Novelty/value – Executive character and Forms Size have no effect on Tax Avoidance, because executives want a good company reputation among stakeholders and there is also no material effect if tax avoidance is carried out